2005
DOI: 10.1007/s10637-005-1442-2
|View full text |Cite
|
Sign up to set email alerts
|

DE-310, a macromolecular prodrug of the topoisomerase-I-inhibitor exatecan (DX-8951), in patients with operable solid tumors

Abstract: These data indicate that there is distribution of DE-310 into tissue and that DX-8951 and G-DX-8951 are released slowly over an extended period from DE-310 providing prolonged exposure similar to a continuous infusion. However, the similarity in the concentrations in tumor and relevant normal tissues does not support the EPR concept in the studied human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Similar results were achieved with DE-310 (see Figure 22), a 340-kDa carboxymethyldextran conjugate of the camptothecin analogue DX-8951, in six patients with different tumors. [128] Although these results are in marked contrast to previous biodistribution studies in tumorbearing animals, [129,130] they should not be overestimated.…”
Section: Passive Targetingmentioning
confidence: 66%
“…Similar results were achieved with DE-310 (see Figure 22), a 340-kDa carboxymethyldextran conjugate of the camptothecin analogue DX-8951, in six patients with different tumors. [128] Although these results are in marked contrast to previous biodistribution studies in tumorbearing animals, [129,130] they should not be overestimated.…”
Section: Passive Targetingmentioning
confidence: 66%
“…A clinical study demonstrated that G-DX-8951 concentration in tumor tissues are approximately ten fold greater than DX-8951, suggesting that G-DX-8951 might partially contribute to the cytotoxic activity of DE-310. 27) Structural requirements for drug release from macromolecular prodrugs have been discussed by Soyez et al 28) who concluded that, whereas general trends could be found, the type of carrier and drug used greatly influences the degradation rate and pattern due to specificities of substrate-enzyme reactions. Taking into account the difference in cytotoxic effects between DX-8951 and G-DX-8951, the present study was initiated to investigate how these two forms appear from DE-310 hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity gives rise to considerable variation in the EPR effect of a tumor at different regions and during different stages. Second, because of the vast difference in the progression rates between frequently studied animal models (usually mouse models) and most human solid tumors, the vasculature in the latter is much more mature and less disorganized, bringing into question the existence of the EPR effect in human patients . Thus, it is still unclear whether the results of EPR‐based nanomedicines tested in animals can be clinically translated.…”
Section: Challenges In the Epr‐based Tumor‐targeted Drug Deliverymentioning
confidence: 99%